PENGUATAN PENGETAHUAN REMAJA PUTRI UNTUK MELAKUKAN PENANGANAN DISMINOREA DENGAN KONSUMSI TEMULAWAK - Munisah Kistriyono; Diyana Faricha Hanum; Alfu Lailah; Hilda Indriani (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2021)
Background: When a person enters adolescence, various changes happen for both physical and mental. In young women, it is shown by the start of the menstrual cycle. At this time, they should get accurate information about the process of menstruation, menstrual disorders that may occur and how to handle those. There are several menstrual disorders, one of them is dysmenorrhea or menstrual pain. Dysmenorrhea forces women to rest or results in reduced daily activities. Objective: To determine the effect of providing material on the treatment of menstrual pain with the consumption of ginger on the knowledge of adolescent girls in Gending Kebomas Village, Gresik. Methods: This study used a sample of young women in Gending Kebomas Gresik Village, amounting to 100 respondents. The analysis used in this study used a bivariate test (paired sample T test). Results: The results shown that the significance was 0.000 so that the results of the bivariate analysis on Adolescent Girls' Knowledge for Handling Dysmenorrhea with Curcuma Consumption (pre and post) shown differences between pretest and posttest results. Conclusion: that the results of the activities carried out by the researchers succeeded in increasing respondents' knowledge about Handling Dysmenorrhea with Curcuma Consumption.